An Affair to remember - Wald, Jerry 1911-1962.; McCarey, Leo.; Daves, Delmer 1904-1977.; Grant, Cary 1904-1986.; Kerr, Deborah 1921-.; Twentieth Century-Fox Film Corporation ([United States] Twentieth Century-Fox Film Corp., 1993)
A handsome bachelor and a cabaret singer meet on a luxury liner bound for New York. Although both are involved with other people, they fall in love. When the ship docks they agree to spend six months apart as a test of their love. But a tragic accident keeps them from their rendezvous and leaves their future uncertain.
DVD
Originally produced as a motion picture in 1957.
Original story by Leo McCarey and Mildred Cram ; director of photography, Milton Krasner.
Cary Grant, Deborah Kerr.
Keywords: Classical drama; Romance drama